2016
DOI: 10.1007/s00396-016-3905-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel cationic Gemini surfactant with amide group: synthesis and micellization behavior in aqueous solutions

Abstract: Novel cationic Gemini surfactant with amide group, N 1 ,N 10 -bis(3-dodecanamidopropyl)-N 1 ,N 1 ,N 10 ,N 10 -tetramethyldecan-1,10-diammonium bromide (abbreviated as 2C 12 enAm) has been synthesized by two-step reactions, purified and characterized in our laboratory. The critical micelle concentration (CMC) values of this Gemini surfactant were determined using electrical conductivity and surface tension measurements in the range of temperatures from 298.15 to 328.15 K. It was observed that the CMC value of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This necessitates the development of a new generation of cationic surfactants having a high surface activity, excellent adsorptive ability, and antibacterial activity. It has been reported that the properties of surfactants can be improved by rationally tuning their molecular structure (Akbaş et al, ; Ding et al, ; Haldar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This necessitates the development of a new generation of cationic surfactants having a high surface activity, excellent adsorptive ability, and antibacterial activity. It has been reported that the properties of surfactants can be improved by rationally tuning their molecular structure (Akbaş et al, ; Ding et al, ; Haldar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The standard Δ G mic o , Δ H mic o , and Δ S mic o of micellization have been calculated with the following equations: …”
Section: Resultsmentioning
confidence: 99%
“…The amido-amine-based cationic Gemini surfactant (Ghumare et al, 2013) was synthesized in two steps (Akbaş et al, 2016).…”
Section: Synthesis Of Gemini Surfactants and Structural Characterizationmentioning
confidence: 99%